Graphics and Multimedia for the Web with Adobe Creative Cloud Navigating the Adobe Software Landscape - Harder, Jennifer (Apress, 2018)
Upgrade your skills in Adobe Creative Cloud and enhance your corporate or personal website with multimedia and graphics. In this book you'll look at the latest versions of five core Adobe programs: Photoshop, Illustrator, Animate (formerly Flash), Media Encoder and Dreamweaver. As you work with each of these programs to create images, animations, audio and video you will see how each one can help you complete and finally integrate your multimedia files into a final mobile friendly website. Adding new multimedia features to your website does not have to be difficult or confusing. If you plan your route and goals correctly, along the way you will see how each software has its own use, but ultimately, how they can all work together for a common goal. This book also shows you how additional Creative Cloud software can be used with the core five programs should you want to add further interactivity.